Constraints, interventions and prospects for improving pearl millet (Pennisetum glaucum L.) production in the state of Eritrea - A review - Oliver Okumu; Philip Wendot; N. Tesfa Michael Abraha (Innovations in Agriculture)
Pearl millet (Pennisetum glaucum L.) is the second most important cereal grown in Eritrea after sorghum (Sorghum bicolor L.) grown under low input systems by small scale farmers. The crop utilizes soil moisture efficiently and has ability to tolerate soil toxicity and extreme temperatures than other cereals. It is a sustenance and food security crop important for its nutritive and cultural value and provides dietary energy and nutrition. However, despite the positive attributes and qualities of pearl millets for the present and future agriculture, production has been low. We attribute this to inadequate rainfall distribution, poor crop management by poorly resourced farmers, unavailability and high prices of farm inputs such as fertilizer and pesticides and low adoption of improved varieties by the farmers. This review outlines the constraints, interventions the government/ farmers have and can implement and the prospects of actions that can improve pearl millet production. As much as there have been efforts by the government and stakeholders to address these challenges and improve productivity of pearl millet, more needs to be done to meet the increasing demand of the increasing populations. This will enable farmers to intensify and diversify their agricultural systems and improve food security situation in the country. Unless a combined effort in soil fertility improvement, policies to promote use of modern varieties and conservation of and promotion of this crop biodiversity, the potential of this crop as famine and poverty alleviation among the rural poor will not be realized.